A framework to understand the design guidelines of smart and sustainable urban open space - Zami, Mohammad Sharif; Qwaider, Sara; Al-Ramadan, Baqer M.; Hassanain, Mohammad A. (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
Smart and Sustainable Urban Open Space (Smart-SUOS) are essential for improving the quality of life (QoL). They serve as hubs for leisure, social interaction, civic activities, and environmental benefits. This study provides a comprehensive overview of the types, design elements, and guidelines necessary to design Smart-SUOS. The study aims to formulate a framework to understand the design guidelines of Smart-SUOS. To achieve the aim, a critical review of the existing literature was carried out. The analysis of the secondary data gathered 13 essential landscape design elements (LDEs), 9 smart services and technology integration, and 10 design conditions (DCs) that were utilized to formulate a design framework of Smart-SUOS. The validated design framework included an additional LDE, 2 smart services and technology integration, and 2 DCs. The framework also includes a series of challenges and measures to overcome the challenges for the successful design of Smart-SUOS.